Perancangan Aplikasi Mobile Game Edukasi Taman Belajar Sebagai Media Pembelajaran Edukatif Anak - Anggi Dwi Nurul Aini; Muhamad Rizki Sulaiman; Risman Risman; Surya Purnama Putra (Universitas PGRI Yogyakarta, 2021)
This research aims to create and know the use of educational games as an alternative learning medium for children. The importance of learning in this child is not accompanied by a media of appropriate child age. In afact, children are more likely to be interested in playing than learning. Therefore, there needs to be learning media that supports the habit of playing in children. In the conventional learning media, children will tend to feel bored because they only learn through books. With the existence of learning media in the form of educational games will facilitate children in the process. The results of this study are educational game products. Software or game engine used in this creation of this educational game is construct 2.